Decreased superficial surgical site infections, shortened hospital stay, and improved quality of life due to incisional negative pressure wound therapy after reversal of double loop ileostomy. Issue 6 (12th February 2018) - Poehnert, Daniel; Hadeler, Nils; Schrem, Harald; Kaltenborn, Alexander; Klempnauer, Juergen; Winny, Markus
Abstract: This single‐center prospective, controlled observational study investigates the impact of incisional negative pressure wound therapy on wound healing processes and its potency to prevent superficial surgical site infections (SSSI) after reversal of a double loop ileostomy. Furthermore, this study gains insight in socioeconomic aspects, like duration of hospital stay and, for the first time, patient's quality of life during the incisional negative pressure wound treatment. To address this question, an interventional group of 24 patients treated with incisional negative pressure wound therapy (Prevena incisional wound management system, KCI, Germany) and a respective control cohort of 25 patients treated with a standard sterile dressing were observed for 30 days in the postoperative course. Postoperative incisional negative pressure wound therapy resulted in statistically significant decreasing duration of hospital stay (6 days vs. 9 days, p  = 0.019) and lower rates of SSSIs (12.5% vs. 20.0%, p  = 0.478) in accordance with a not statistically significant decreased necessity of postoperative antibiotic therapy (12.5% vs. 36%, p  = 0.051). To survey subjective items of well‐being and quality of life, all patients were asked to answer a questionnaire. Patients of both groups noticed increasing quality of life after reversal of their ileostomy. However, patients treated with an incisional negative pressure wound therapy had a superior improvement of a variety of subjective items, resulting in an overall much better satisfaction with the course of wound healing. Our findings suggest, that incisional negative pressure wound therapy seems to be a reasonable therapeutic option to reduce incidence of SSSIs and to have a beneficial impact to patient's quality of life, as well as, socio‐economic aspects.